Assessment of Physiological Amplitude, Duration, and Magnitude of ECG T‐Wave Alternans - Burattini, Laura (Ann Noninvasive Electrocardiol, 2009)
Background: An association between T‐wave alternans (TWA) and malignant ventricular arrhythmias is generally recognized. Because relatively low levels of TWA have also been observed in healthy (H) subjects, the question arises as to whether these are ascribable to noise and artifacts, or can be given the relevance of a physiological phenomenon characterizing a preclinical condition. Methods: To answer this question, in the present study 20‐minute not noisy, sinus ECG recordings, from 138 H‐subjects and 148 coronary artery diseased (CAD) patients, were submitted to our adaptive match filter (AMF) procedure to identify and parameterize TWA in terms of duration (TWAD), amplitude (TWAA), and magnitude (TWAM, defined as the product of TWAD times TWAA). The 99.5th percentiles of mean values of TWAA, TWAD, and TWAM over 20‐minute ECGs were used to define three threshold levels (THRD, THRA, and THRM), which allow discrimination of abnormal TWA levels. Results: Nonstationary TWA was found in all our H‐subjects and CAD‐patients. TWAD, TWAA, and TWAM levels were classified as being physiological in 99% of H‐subjects and 87% of CAD‐patients. A linear correlation (r =−0.52, P < 0.001) was found between TWAA and RR interval in the H‐population. Conclusions: Our results support the hypothesis of the existence of physiological TWA levels, which are to be considered in the effort to improve reliability of nonphysiological TWA levels discrimination.